Librarians Empathy: Visually Impaired Students' Experiences Towards Inclusion and Sense of Belonging in an Academic Library - Bodaghi, N.B.; Loh, S.C.; Zainab, A.N. (Elsevier, 2016)
One of the key factors that fosters the creation of a sense of belonging is the sense of empathy. Indeed, it is considered to be one of the key skills for helping professionals, especially librarians. Nevertheless, previous studies were mostly library-focused. This paper approaches this issue from the visually impaired person's (VIP) perspective. The questions this paper aims to answer are: “What have VIPs experienced in a University library regarding the degree of librarians' sense of empathy” and, “How do they perceive it?” This study uses a qualitative approach. Data was collected through interviews and focus group discussions with eighteen VIPs who were registered in a university library. To determine the trustworthiness of the data, member checking, external audit, and reflexivity were used. The participants of the study perceived librarians' greeting and friendly conversation, their tone of voice, sense of understanding regarding their limitations, and their communication regarding any changes in the circumstance of the library environment as key factors that illustrate their sense of empathy towards VIPs. Furthermore, VIPs expressed being afraid to ask for help from librarians, being disappointed, confused, uncomfortable, and not being understood due to a lack of librarians' sense of empathy that influenced their professional behavior.